Sulfur and Calcium Simultaneously Regulate Photosynthetic Performance and Nitrogen Metabolism Status in As-Challenged Brassica juncea L. Seedlings - Singh, Rachana; Parihar, Parul; Prasad, Sheo M. (Frontiers in Plant Science, 2018)
In the present study, the role of sulphur (K2SO4: S; 60 mg S kg־1 sand) and/or calcium (CaCl2: Ca; 250 mg Ca kg־1 sand) applied alone as well as in combination on growth, photosynthetic performance, indices of chlorophyll a fluorescence and nitrogen metabolism of Indian mustard (Brassica juncea L.) seedlings in absence or presence of arsenic (Na2HAsO4.7H2O: As1; 15 mg As kg־1 sand and As2; 30 mg As kg־1 sand) stress. Arsenic with its rising concentration negatively affected the fresh weight, root/shoot ratio, leaf area, photosynthetic pigments, photosynthetic oxygen yield and chlorophyll a fluorescence parameters: the O—J, J—I and I—P rise, QA⁻ reoxidation kinetics i.e. ФP0 or Phi_P0, Ψ0 or Psi_0, ФE0 and PIABS, while increased the energy flux parameters i.e. ABS/RC, TR0/RC, ET0/RC and DI0/RC due to higher As/S and As/Ca ratio in root followed by shoot; however, exogenous application of S and Ca and their combined effect too, notably counteracted on As induced toxicity on growth and other important growth regulating processes. Moreover, inorganic nitrogen contents i.e. nitrate and nitrite and the activities of nitrate assimilating enzymes viz., nitrate reductase (NR), nitrite reductase (NiR) and ammonia assimilating enzymes viz., glutamine synthetase (GS) and glutamate synthase (GOGAT) were severely affected with As toxicity; while under similar condition, ammonium content and glutamate dehydrogenase (GDH) activity in both root and leaves showed reverse trend. Furthermore, when S and Ca applied either alone or in combination to As stressed test seedlings, a significant amelioration in the above mentioned parameters was noticed except in NH4+ content and GDH activity, which showed an obvious reduction under similar conditions. These findings point out that exogenous application of S and/or Ca particularly S+Ca more favourably regulated the photosynthesis, contents of protein, carbohydrate, inorganic nitrogen and activities of nitrate and ammonia assimilating enzymes, which might be linked with the mitigation of As stress. Our results suggest that exogenous application of S+Ca more efficiently defends Brassica seedlings by declining As accumulation in root and shoot tissues and by maintaining the photosynthesis and nitrogen metabolism as well.